Self‐Assembled Multilayer‐Stabilized Nickel Nanoparticle Catalyst for Ligand‐Free Cross‐Coupling Reactions: in situ Metal Nanoparticle and Nanospace Simultaneous Organization. Issue 15 (27th April 2016) - Hoshiya, Naoyuki; Fujiki, Katsumasa; Taniguchi, Takahisa; Honma, Tetsuo; Tamenori, Yusuke; Xiao, Mincen; Saito, Nozomi; Yokoyama, Mami; Ishii, Akira; Fujioka, Hiromichi; Shuto, Satoshi; Sato, Yoshihiro; et al.
Abstract: We have developed a conceptually and methodologically novel self‐assembled multilayer nickel nanoparticle (NP) catalyst – sulfur‐modified gold‐supported Ni NPs (SANi) – for organic synthesis. The SANi catalyst was easily prepared through a three‐step procedure involving simultaneous in situ metal NP and nanospace organization. This unique method does not require any conventional preformed template for immobilizing and stabilizing NPs. SANi catalyzes carbon‐carbon bond‐forming cross‐coupling, Kumada coupling, and Negishi coupling reactions under ligand‐free conditions and can be used repeatedly for these reactions. Physical analysis of SANi showed that the active species in these reactions are self‐assembled multilayer zerovalent Ni NPs with a size of ∼3 nm. Abstract :